Pengelolaan Sampah dan Keberkahan Lingkungan Hidup Perspektif Fikih - Abd Rahman R (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
Waste management is an urgent global issue, considering its impact on the quality of the environment and the sustainability of human life. This research aims to explore waste management based on fiqh principles, including sharia rules such as la darara wa la dirar (no harm and no harm to each other) and maslahah mursalah (public benefit) with a normative theological approach of qualitative analysis. The results of the study show that fiqh teaches waste management as a form of human responsibility as a caliph on earth, which is realized through the reduction, reuse, and recycling of waste (3R) within the framework of sustainability. In addition, there is the potential for blessings that can be achieved through proper waste management, both in the form of social impacts, such as improving the quality of public health, and spiritual impacts, such as getting closer to Allah by maintaining His mandate. This study concludes that the fiqh approach to waste management not only provides practical solutions to the environmental crisis, but also builds the spiritual and ecological awareness of Muslims to create harmony with nature. This study recommends the integration of fiqh principles in waste management policies, in order to create a blessed and sustainable living environment.